What’s in a Name? The Case of Emotional Disclosure of Pain-Related Distress - Cano, Annmarie (J Pain, 2017)
Pain behavior plays a key role in many theoretical models of pain, with many of these models conceptualizing pain behaviors as potentially detrimental to patient functioning. We propose that a certain class of behaviors—talking to others about one’s pain-related distress (i.e., emotional disclosures of pain-related distress)—can be distinguished from other behaviors traditionally conceptualized as pain behaviors. Emotional disclosures of pain-related distress include verbally disclosing one’s anger, sadness, or worry about the pain and its impact to another person. In this article, conceptual and empirical evidence is offered to indicate that these verbal behaviors are distinct from other pain behaviors such as bodily expressions and motions, facial expressions, pain ratings, and paraverbal expressions. Emotion and relationships models are also applied to assert that disclosures of pain-related distress may have functions that are not shared with other pain behaviors. In addition to an expanded conceptualization of these verbal expressions of distress about pain, further directions are provided to spur new research as well as clinical recommendations concerning appropriate responses to these behaviors. PERSPECTIVE: This article offers an expanded conceptualization of one type of pain behavior—emotional disclosure of pain-related distress—by demonstrating the theoretical and empirical distinctions between this behavior and other pain behaviors. This perspective may enhance clinical work and research aimed at identifying adaptive responses to these behaviors to improve pain adjustment.